Extrusion of Irrigant in Open Apex Teeth with Periapical Lesions Following Laser-Activated Irrigation and Passive Ultrasonic Irrigation - Peeters, Harry Huiz; Suardita, Ketut; Mooduto, Latief; Gutknecht, Norbert (Iranian Endodontic Journal, 2018)
Introduction: Sodium hypochlorite (NaOCl) irrigation is critical for the success of endodontic treatment and several agitation techniques have been developed to improve the efficacy of this irrigation. Using a combination of contrast medium and radiographic examination, this study evaluated NaOCl extrusion during agitation of irrigant. Development of pressure, which may result in apical extrusion of the irrigant, has been described during laser-activated irrigation (LAI) and passive ultrasonic irrigation (PUI). Methods and Materials: We examined 40 single root canals categorized as having open apices with apical lesions in 40 patients. For the final irrigation, the teeth were irrigated with a mixture of radiopaque contrast medium and 2.5% NaOCl in solution. The solution was activated for 60 sec in both groups [the Er, Cr: YSGG laser group (n=20) and the ultrasonic group (n=20)]. The teeth were imaged subsequently using radiography for the evaluation of contrast extrusion. Results: Radiopaque contrast medium was absent from the periapical tissues in all cases. Conclusion: Use of LAI or PUI appears to be safe as used currently in endodontic treatment. Keywords: Endodontics; Er, Cr: YSGG Laser; Open Apex; Periapical Lesion